NiRu0.3Se Nanoparticles In Situ Grown on Reduced Graphene: Synthesis and Electrocatalytic Activity in the Oxygen Evolution Reaction. Issue 3 (19th January 2021) - Mehmood, Adeel; Ur‐Rehman, Zia; Altaf, Muhammad; Ashraf, Raja Shahid; Sohail, Manzar; Isab, Anvarhusein A.
Abstract: Nanoscale transition metal selenides have been tagged as promising electrocatalytic materials for efficient energy conversion. Herein, we report the facile hydrothermal synthesis of NiRu0.3 Se nanoparticles, in situ grown on reduced graphene oxide, for oxygen evolution reaction (OER) in water splitting. The crystal phase, morphology and elemental composition of NiRu0.3 Se/rGO is well characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), X‐ray photoelectron spectroscopy (XPS) and energy dispersive X‐ray spectroscopy (EDX). The composite exhibited hexagonal and cubic phase structure corresponding to NiSe and RuSe2, having irregular morphology. NiRu0.3 Se/rGO exhibited superior OER performance than NiSe/rGO requiring an overpotential of 290 mV to generate a benchmarked current density of 10 mA cm −2 in 0.1 M KOH. A small tafel slope of 98 mV dec −1 and long‐term stability endorses the potential of NiRu0.3 Se/rGO as an efficient OER electrocatalyst. Abstract : Nanoscale transition metal selenides are promising electrocatalytic materials for efficient energy conversion applications. Synthesis of NiRu0.3 Se nanoparticles, in situ grown on reduced graphene oxide, for oxygen evolution reaction (OER) are reported here. The composite exhibited hexagonal and cubic phase structure corresponding to NiSe and RuSe2, having irregular morphology. NiRu0.3 Se/rGO exhibited superior OER performance than NiSe/rGO requiring an overpotential of 290 mV to generate a benchmarked current density of 10 mA cm −2 in 0.1 M KOH.